Experimental verification of railway substructure with application of reinforced geocomposite - Izvolt, Libor; Mecar, Martin (Communications - Scientific Letters of the University of Zilina, 2004)
In the paper the authors present results of experimental measurements realized in a testing stand which was built for evaluation of reinforced effect of geocomposite MACRIT GTV/50-50 B applied into a railway substructure. Methodology of experimental measurements, observed physical characteristics of used grounds and results of static loading tests for various granularity and thickness of subbase material (150 mm -600 mm) are described. The main result of the experimental evaluation of two-tested subbase materials is a proposal of nomograms for dimensioning the railway substructure with application of topical geosynthetic material.
Keywords: no keywords